William Horbury, Jewish War under Trajan and Hadrian (Cambridge: Cambridge University Press, 2014) - Rosik, Mariusz (The Biblical Annals, 2015)
Book review: William Horbury, Jewish War under Trajan and Hadrian (Cambridge: Cambridge University Press, 2014). Pp. 501 + X. 4 maps. 110. ISBN 978-0-521-62296-7 (Hardcover).